2017
DOI: 10.1039/c6bm00939e
|View full text |Cite
|
Sign up to set email alerts
|

A novel botryoidal aramid fiber reinforcement of a PMMA resin for a restorative biomaterial

Abstract: Poly(methyl methacrylate) (PMMA) resin is widely used as a prosthetic and restorative biomaterial, such as in bone cement, denture base resin, etc. The flexural and compressive strength of a PMMA resin is of great concern and many approaches have been made to improve the flexural resistance and compressive strength of PMMA. To strengthen PMMA via high-performance (HP) fibers is a feasible way; however, the HP fibers are not very satisfactory in practice, with a complex handling process and esthetic concerns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The denture base materials can be strengthened to prevent fractures which is a common complication. There are some studies that have evaluated the effect of reinforcement of PMMA with different materials, but the those on the reinforcement of polyamide resin are scarce ( 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 33 ). In a previous study, the rigidity of dentures made of polyamide, polyester and conventional heat-polymerized PMMA were compared, and it was concluded that the polyamide, which has low elasticity, needed to be reinforced with metal frames ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The denture base materials can be strengthened to prevent fractures which is a common complication. There are some studies that have evaluated the effect of reinforcement of PMMA with different materials, but the those on the reinforcement of polyamide resin are scarce ( 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 33 ). In a previous study, the rigidity of dentures made of polyamide, polyester and conventional heat-polymerized PMMA were compared, and it was concluded that the polyamide, which has low elasticity, needed to be reinforced with metal frames ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been developed to overcome these disadvantages such as; adding filling materials to reinforce of resins, chemical modifications of polymer with copolymerization and cross-linking of resin materials, producing new materials with different polymerization technics ( 6 , 7 , 8 ). Strengthening materials such as glass fiber, aramid fiber, nanodiamond powder, zirconium oxide, aluminum oxide, halloysite nanotubes, metal wires and carbon nanotubes can be added to denture base in order to increase fatigue resistance and fracture resistance of the prosthetic base materials ( 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ). However, the most effective reinforcement is yet to be determined ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…A popular way of enhancing the mechanical properties of PMMA involves producing composite materials with microfillers, such as glass [ 5 ], polyethylene [ 6 ], aramid fiber [ 7 ], carbon fiber [ 8 ], silica or glass particles [ 8 , 9 ], and stainless steel mesh [ 10 ]. According to previous studies [ 5 , 6 , 7 , 8 , 9 , 10 ], these fillers slightly increase the flexural and impact strengths of PMMA; however, their use is limited because the addition of the filler generally reduces the transparency of the polymer [ 9 ], which is one of the most important features of PMMA resin. At the same time, the formation of a PMMA/filler interface often reduces the tension strain limit owing to the effects of structural heterogeneity and interfacial adhesion [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the formation of a PMMA/filler interface often reduces the tension strain limit owing to the effects of structural heterogeneity and interfacial adhesion [ 11 , 12 , 13 ]. Therefore, various types of micro- and nanofiber, including carbon, aramid, and ultra high-molecular-weight polystyrene, have been investigated as reinforcing fillers that enhance the mechanical properties of PMMA [ 7 , 8 , 14 ]. Unfortunately, these fillers absorb stress and energy inadequately, which leads to structural deficiencies, a lack of rigidity, and inhomogeneous filler setting that, in turn, result in a fragile and fractured composite [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intensive research is currently being conducted to improve the thermal, mechanical and biological properties of bone cements [ 16 ]. The research includes doping the cement mass with small amounts of components such as carbon fibers [ 41 ], zirconia fibers [ 42 ], graphite fibers [ 43 ], graphene oxide [ 44 , 45 , 46 , 47 ], bioactive glasses [ 48 ], nanosilver [ 49 ], polydioxanone (PDO) [ 48 ], cellulose [ 48 , 50 , 51 ], mesoporous silica nanoparticles [ 52 , 53 ], aramid [ 54 , 55 ], polyethylene [ 56 ], titanium [ 57 , 58 ], ultra-high molecular weight polyethylene [ 59 ], tricalcium phosphate (TCP) [ 16 , 60 ] or hydroxyapatite (HA) [ 61 , 62 ]. The effect of aging processes associated with the absorption of physiological fluids and the accompanying hydrolysis of polymethylmethacrylate (PMMA) occurring in the outermost layers of the cement are also important, as well as the effect of deviation from the manufacturer’s recommended cement mix ratio [ 63 , 64 , 65 , 66 , 67 ].…”
Section: Introductionmentioning
confidence: 99%